Migration and Post-Conflict Reconstruction: The Effect of Returning Refugees on Export Performance in the Former Yugoslavia - Dany Bahar; Cem Özgüzel; Andreas Hauptmann; Hillel Rapoport (Institute of Labor Economics (IZA), 2019)
During the early 1990s Germany offered temporary protection to over 600,000 Yugoslavian refugees fleeing war. By 2000, many had been repatriated. We exploit this natural experiment to investigate the role of migrants in post-conflict reconstruction in the former Yugoslavia, using exports as outcome. Using confidential social security data to capture intensity of refugee workers to German industries–and exogenous allocation rules for asylum seekers within Germany as instrument—we find an elasticity of exports to return migration between 0.08 to 0.24. Our results are stronger in knowledge-intensive industries and for workers in occupations intensive in analytical and managerial skills.
Keywords: O33; F14; F22; 330; migration; refugees; knowledge diffusion; management; exports; productivity